Effect of proprotein convertase subtilisin/kexin type 9 inhibition on cancer events: A pooled, post hoc, competing risk analysis of alirocumab clinical trials - Kusha A. Mohammadi; Taylor Brackin; Gregory G. Schwartz; Philippe Gabriel Steg; Michael Szarek; Garen Manvelian; Robert Pordy; Sergio Fazio; Gregory P. Geba (Cancer Medicine, 2023)
Abstract Objective Assess the risk of new and worsening cancer events among participants who received the lipid‐lowering therapy alirocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor. Design Pooled post hoc analysis. Setting Six phase 3 or phase 4 placebo‐controlled randomised trials with alirocumab. Participants A total of 24,070 patients from the safety population with complete dosing data (alirocumab, n = 12,533; placebo, n = 11,537). Intervention Alirocumab 75 mg, alirocumab 150 mg, alirocumab 75 mg increasing to 150 mg if low‐density lipoprotein cholesterol <50 mg/dL not achieved, or placebo, all every 2 weeks. All participants received background high‐intensity or maximum‐tolerated statin therapy. Outcomes and Measures The first new or worsening incident cancer events were assessed during the treatment‐emergent adverse event period. Four outcomes were evaluated: any‐neoplasm, malignant neoplasms, broad definition of hormone‐sensitive cancers, and stricter definition of hormone‐sensitive cancers. Sub‐distribution hazard ratios and 95% confidence intervals (CIs) were estimated using a competing risk framework, with death as a competing risk. Results Considering both treatment arms in aggregate, 969 (4.03%), 779 (3.24%), 178 (0.74%) and 167 (0.69%) patients developed any neoplasm, malignant neoplasms, broad definition of hormone‐sensitive cancer and strict definition of hormone‐sensitive cancer events, respectively. There was no significant difference in the risk of having any neoplasm in the alirocumab versus the placebo group (sub‐distribution hazards ratio [95% CI], 0.93 [0.82–1.1]; p = 0.28). A nominally lower risk of having any neoplasms with alirocumab was observed among subjects aged ≥64 years (sub‐distribution hazards ratio 0.83; 95% CI, 0.70–0.99). Conclusions Intensive low‐density lipoprotein cholesterol lowering with a proprotein convertase subtilisin/kexin type 9 inhibitor combined with statin does not appear to increase the risk of new or worsening cancer events.